P165 Comparison of postoperative complications and quality of life between patients undergoing continent versus non-continent urinary diversion after pelvic exenteration. (1st November 2019) - Mallet, E; Angeles, MA; Cabarrou, B; Rouanet, P; Méeus, P; Lambeaudie, E; Classe, JM; Foucher, F; Narducci, F; Migliorelli, F; Martínez-Gómez, C; Gladieff, L; et al.
Abstract : Introduction/Background: Pelvic exenteration remains as the only curative treatment for patients with recurrent or persistent pelvic disease after prior radiotherapy for gynecologic malignancies. The aim of our study was to compare postoperative complications and quality of life (QoL) of patients undergoing continent versus non-continent urinary diversion after pelvic exenteration. Methodology: We designed a multicentric French study, including patients from ten centers who underwent an anterior or total pelvic exenteration with urinary reconstruction for persistent or recurrent gynecologic malignancy after prior radiotherapy. From January 2005 to September 2008 we included patients retrospectively, and from September 2008 to May 2009 they were prospectively included, which allowed us to collect QoL data. Demographic, surgical and follow-up data were analyzed. Postoperative complications were classified following Clavien-Dindo Classification. QoL was assessed using the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 (version 3.0) and the EORTC QLQOV28 questionnaires. Results: A total of 148 patients were included, 92 retrospectively and 56 prospectively. Among these patients, 70 underwent a urinary continent diversion and 78 patients a non-continent diversion. There were no differences between continent and non-continent groups in hospitalization length, postoperative grade III-IV complications, complications needing surgical or radiological intervention and complication type (digestive, urinary, parietal, infectious, hemorrhagic or medical). As well, there were no significant differences in QoL. Conclusion: Continent and non-continent urinary diversion seems to be equivalent in terms of QoL and postoperative complications. However, global health and QoL in continent group appears to be worse one month after surgery, with a slight long-term improvement when compared to the non-continent group. Body image perception seems to be better in non-continent group one month after surgery with a progressive long-term deterioration, while continent group acquired a better body image perception three months after surgery, which stabilized in the long-term. Disclosure: Nothing to disclose.